An integrative review of resilience among nursing students in the context of nursing education - Pimwalunn Aryuwat; Margareta Asp; Annica Lövenmark; Matanee Radabutr; Jessica Holmgren (Wiley, 2023)
Abstract Aim This integrative review aimed to examine empirical research on resilience among nursing students in the context of nursing education. Resilience helps nursing students handle challenges, such as changing learning styles and experiencing their first clinical practice. Design An integrative review. Methods The search terms focused on resilience and health in nursing students and nursing education. The database used in this review were CINAHL Plus, PubMed and MEDLINE. The Mixed Methods Appraisal Tool appraised the studies' quality. Results This study explored 52 records and revealed three current research focuses related to nursing students' resilience: (1) the concept and description of resilience, (2) the characteristics affecting resilience and (3) the mediating role of resilience in maintaining holistic health. Recommendations include adding a resilience topic to the nursing curriculum, providing resilience enhancement programs, examining the relationship between resilience and holistic health and exploring the influence of resilience about global health crises. Public Contribution Resilience among nursing students plays a vital role in helping them to overcome adversities during their nursing education. Additionally, after graduation, nursing students can continue contributing to society as resilient Registered Nurses in the future.